An extensive study on the COVID-19 pandemic, an emerging global crisis: Risks, transmission, impacts and mitigation. Issue 2 (February 2021) - Parthasarathy, P.; Vivekanandan, S.
Abstract: A number of unexplained cases of pneumonia have been recorded since November 2019 in China. It is officially named the new corona virus (2019-nCov) by the World Health Organization on 12 January 2020. WHO officially named it COVID-19 on 11 February. COVID-19 is a highly transmitted and pathogenic viral infection that has been developed and spread across the world in Wuhan, China, caused by extreme acute respiratory syndrome corona-virus 2 (SARS-CoV-2). Genomic analysis showed that bats may also be a primary reservoir of SARS-CoV-2 phylogenetically associated with severe acute respiratory syndrome-like viruses (SARS). However, the rapid human to human transition has been generally reported. Intermediate source of origin and human transition is unknown. Clinically approved COVID-19 antiviral medication or vaccine is not available. In clinical trials, however, few broad-based COVID-19 antiviral medicinal drugs were tested, resulting in clinical recovery. This analysis summarizes the pathogenicity of COVID-19 and aims to raise awareness of COVID-19 among the population and to continually boost the detection, monitoring, diagnosis and care level. Over 50 COVID-19 scientific publications were included in this systematic analysis. We found that fever (87.0%), cough (65.9%) and malaise/tiredness (35%) were the most common symptoms of COvida-19. However, COVID-19 clinical signs and symptoms were not necessarily obvious. The transmission of COVID-19 in comparison to SARS was more specific. The rate of death of COVID-19 was 2, 7% and the pathological characteristics of COVID-19 are very similar to ARDS. There are also discussions on the latest epidemiological changes, clinical manifestations, auxiliary examination and COVID-19 pathological characteristics.